Migration of formaldehyde and melamine from melaware and other amino resin tableware in real life service. Issue 1 (2nd January 2017) - Mannoni, Veruscka; Padula, Giorgio; Panico, Oronzo; Maggio, Antonino; Arena, Claudio; Milana, Maria-Rosaria
ABSTRACT: The migration of formaldehyde and melamine monomers has been measured on 90 samples of plastic tableware in three different situations – new articles, already used articles and artificially aged articles – by using simulant, contact times and temperatures prescribed by Commission Regulation (EU) No. 10/2011. Formaldehyde was determined by ultraviolet spectroscopy analysis of the coloured complex obtained by reaction with chromotropic acid. Melamine was measured by an ultra high performance liquid chromatography method. Fourier Transformed – Infrared Analysis was applied to characterise the plastic. The results highlighted the presence of different amino resins based on formaldehyde-melamine, urea-formaldehyde or melamine-urea-formaldehyde with different migration behaviour. The migration of monomers was related to progressive degradation of the resins. Ageing studies demonstrated that the potential degradation of the resins and the consequent migration of the monomers may continue throughout the service life of the product. The specific migration limit (SML) of melamine was exceeded after ageing.